'Creating a little bit of La Dolce Vita'. Explaining resilience and transformation in the Hunter Valley wine region, NSW, Australia. (8th November 2019) - Grimstad, Sidsel; Waterhouse, Jennifer; Burgess, John
Using the Hunter Valley wine region as a case study, this paper examines how a region, renowned internationally for specific wine varieties, reinvents itself through becoming a gastronomic landscape. Using a case study approach, this paper identifies, through qualitative data how, in spite of being a small national producer, the Hunter Valley still strongly identifies with and protects its wine-region identity. The importance of having regional identity 'custodians' such as the old wine families that ensure that the landscape maintains the rural aesthetic, creates embedded institutions that benefit both old and new entrants. While new entrants may be considered a risk, they also provide a continuous stream of creative solutions and investments, leading to continuous improvement of quality and luxury provision of wine and gastronomy sensory experiences. Hunter Valley wine-tourism actors have contributed to its resilience through simultaneously maintaining a strong wine region identity, while at the same time using this as a means to regenerate itself into a gastronomic landscape where lifestyle, food, wine and tourism complement each other. Through this the Hunter Valley manages to maintain its lead among the top Australian destinations for both national and international wine and food tourists.